Is the Flat Open-Economy Phillips Curve Deceptive Illusion? - Nowak, Dominik (Czy krzywa Philipsa naprawdę może być płaska w obliczu globalizacji?, 2009)
The main purpose of following article is to highlight potential modern Phillips curve augmentation caused by globalization. Although there was a lot of discussion about so called "flattered" curve, the author of the article has decided to present a different approach to relevant matter. Along with a brief presentation of theoretical background behind open- economy of Phillips curve this paper treats new macro-foundations, strictly related with globalization, which may be responsible for accelerating inflation in emerging countries, both in short and long perspective. Above all the contents of the article should not be considered as direct opposition to the New Keynesian modern Phillips curve theory, but rather as a modest follow-up.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 103-116
Keywords: inflation; Phillips curve; Keynes